Binding of Progesterone to Neisseria gonorrhoeae and Other Gram-Negative Bacteria - Miller, Richard D. (1977)
The binding of [1,2-(3)H]progesterone to progesterone-sensitive Neisseria gonorrhoeae CS-7 and the progesterone-insensitive Neisseria mucosa, Pseudomonas aeruginosa, and Salmonella typhimurium (rough and smooth strains) was investigated. The kinetics of binding to N. gonorrhoeae CS-7 demonstrated that the majority of the progesterone binding occurred and equilibrium was reached within the first 30 min. Despite the rapid binding of progesterone, only about 20% of the added steroid was bound at the cell concentration used throughout this study. Whole cells of progesterone-insensitive bacteria bound progesterone less efficiently than the progesterone-sensitive N. gonorrhoeae CS-7. N. mucosa bound low amounts of this steroid (20% of that bound by N. gonorrhoeae CS-7) whereas the other gram-negative bacteria exhibited little progesterone binding (<3% of that bound by N. gonorrhoeae CS-7). The outer membrane permeability of N. gonorrhoeae CS-7, as measured by crystal violet uptake and inhibition, was similar to the deep rough mutant of S. typhimurium TA 1535. The latter organism neither bound nor was inhibited by progesterone. However, isolated cell envelopes of N. gonorrhoeae and progesterone-insensitive bacteria all bound progesterone equally well. Cortisone and cholesterol, althouh structurally similar to progesterone, were not inhibitory to N. gonorrhoeae and did not bind to whole cells as well as progesterone. The major site of progesterone binding appeared to be the cytoplasmic membrane, which bound four times more progesterone than the outer membrane. In addition, isolated cytoplasmic membrane proteins bound more than three times more progesterone per milligram of protein than the intact membrane.